Rapid assessment of safe injection practice in a tertiary care hospital of Eastern India - Panda, Sadhu Charan (International Journal Of Community Medicine And Public Health, 2017)
Background: Unsafe injection practice is harmful to the patients, providers and community especially in a tertiary care hospital. On this backdrop, a rapid assessment of injection practice has been conducted with aim of identifying determinants and indicators of safe injection practice. Methods: A cross sectional study was conducted among 20 providers, 20 prescribers, 100 prescriptions and 120 general population by convenient sampling as per WHO from November 2016 to April 2017 in the hospital of VSS Institute of Medical Sciences & Research, Burla using interview, observation method and analysis of prescriptions. Results: Knowledge about possibility of transmission of HCV due to unsafe injection practice was 80% among providers and 40% among general population. All providers were using sterile syringe and needle though 60% of them were seen not using gloves in case IV Injection/blood transfusion and needle recapping was done by half of them 100 per cent of injection providers reported that they have access to a sharps waste disposal facility. Needle recapping was done by half of them. OT8 indicator was 26.7(%). Average number of injections per person based on the population data was 1 injection per annum. Conclusions: Unsafe injection practice has to be tackled by CME among prescribers about rationale use of injections, antibiotics from essential drug list, regular supply of equipment and hub cutter and education of providers and people about injection safety will prevent avoidable communicable diseases.